Adsorption of mixed surfactants at the oil-water interface - Staples, E; Penfold, J; Tucker, I (2000)
The adsorption of the mixed nonionic/anionic surfactants of hexaethylene glycol monododecyl ether (C12E6) and sodium dodecyl sulfate (SDS) at the hexadecane/water interface has been measured. Small-angle neutron scattering (SANS) in combination with hydrogen/deuterium isotopic substitution, has been used to obtain the structure and composition of the adsorbed mixed surfactant layer at the hexadecane/water interface of a hexadecane in water emulsion, and of the mixed micelles in equilibrium with the emulsion. Measurements of the adsorption of SDS alone have established the experimental approach, and the analysis procedures used. The adsorption isotherm obtained for the SDS from the SANS data is in good agreement with that obtained from surfactant electrode measurements. The SANS data show clearly the point at which, with increasing surfactant concentration, free micelles are formed in equilibrium with emulsion droplets. The variation of the composition of the adsorbed layer for the C12E6SDS mixture at the hexadecane/water interface is not consistent with that previously obtained at the air-water interface, or in mixed micelles. Furthermore, it is not consistent with the straightforward application of theories, such as regular solution theory. The evolution of composition with concentration can be explained if it is assumed that there is partitioning of the C12E6 into the oil phase, and that some solubilization of hexadecane into the mixed micelles takes place. Analysis of the scattering data for the micelles in equilibrium with the emulsion confirms the latter of these two assumptions. On the basis of the data obtained, we have also been able to estimate directly the monomer concentrations of the surfactants in both the oil and water phases.